Library Automation: Design, Principles and Practice. by L.j. Haravu. Allied Publishers, New Delhi, 2004. Pp Xiv + 262. (paper Back, Cd Included) Rs. 450/- [isbn: 81-7764-645-1]. - Ravichandra Rao, I. K. (Journal of Information and Knowledge, 2014)
No Abstract